When to invest in high-speed rail - Christopher Nash (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
High speed rail (HSR) is usually regarded as services operating at 250 kmph or more, and these invariably require construction of new purpose-built lines. According to the International Union of Railways (UIC), by 2012, a total of 13 000km of such lines had been built worldwide, half in Europe and half in Asia. China had the largest network at 3 426km, whilst Japan, France and Spain all had over 2 000km. There are plans for a further major expansion, with the European Commission calling for a trebling of the kilometrage in Europe by 2030.Yet high speed rail is an enormous investment, with a typical 500km line costing 6-12Bn euros in 2004 prices (Euros 12-24 Bn per km) (de Rus and Nash, 2009). It is necessary to consider very carefully in what circumstances such an outlay is justified.
Keywords: 330